Tolerance Peculiarities to Uncertainty of Working Students - Милославська, Олена Володимирівна; Гуляєва, Олена Володимирівна; Сапьян, Євгенія Олександрівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article covers results of an empirical study of the characteristics of tolerance to uncertainty of working students. The sample consisted of 44 participants - students of the V.N. Karazin Kharkiv National University. The first group consisted of 22 subjects who combine their studies at a higher educational institution with work, the second group - 22 subjects who do not work. Tolerance for uncertainty was measured by «Multiple Stimulus Types Ambiguity Tolerance Scale-I» (D. McLain, the adaptation by E. Osin) and «New questionnaire of tolerance for uncertainty» (T. Kornilova). Student's t-test for independent samples was used for statistical processing of the results. Findings of the study revealed that working students have a more positive attitude to new events, a deeper awareness of themselves as the subject of their own actions, and confidence that they control their lives, a greater tendency to make choices quickly and flexibly and the ability to maintain a vision of many opportunities, and greater tolerance for uncertainty in general. For these subjects are more inherent in the desire for change, novelty and originality, willingness to follow unpaved paths and prefer more complex tasks, to be able to be independent of the accepted limitations. Non-working students are characterized by a more pronounced desire for clarity and control in interpersonal relationships and a sense of discomfort in the event of uncertainty in relationships with others. The results obtained make it possible to improve the theoretical understanding of the characteristics of manifestations of tolerance to uncertainty at a student age, determine the prospects for further scientific research and can be used in practical psychological and pedagogical work with students.